Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I've been banging my head against the wall for a while now:

$x = s^2 - t^2$

$y = s + t$

$z = s^2 + 3t$

Express $z$ in terms of $x$ and $y$.

share|improve this question
    
This is homework, right? What have you tried? –  jd.r Apr 27 '11 at 3:38
    
Yeah, this is homework. I have tried combinations of $x^2$, $y^2$, $z^2$, as well as other combinations of powers. I've also tried multiplications of x and y. –  Sir Winford Apr 27 '11 at 3:40
    
If this is homework, you should use the [homework] tag. I've added it for now. –  Arturo Magidin Apr 27 '11 at 3:42
    
Duly noted. Thanks! –  Sir Winford Apr 27 '11 at 3:45

3 Answers 3

up vote 9 down vote accepted

Hint: What is $\dfrac{x}{y}$ equal to?

share|improve this answer
    
$x/y$ = $s - t$ I've done that and tried incorporating it but just don't see how it works. –  Sir Winford Apr 27 '11 at 3:44
3  
If you know $s-t$ and $s+t$ then surely you can find $s$ and $t$. –  Emre Apr 27 '11 at 3:50
8  
Follow up question - what's $(s + t) + (s - t)$ equal to? –  Hans Parshall Apr 27 '11 at 3:59
    
@Hans: great question (+1) –  Fabian Apr 27 '11 at 5:35

$$x=s^{2}-t^{2}=(s+t)(s-t)$$ so $$s+t=\frac{x}{s-t}$$ $$s-t=\frac{x}{s+t}=\frac{x}{y}$$

$$(s+t) + (s-t) = 2s=\frac{x}{s-t}+\frac{x}{y}$$ $y=s+t$, so $t=y-s$ and therefore: $$2s=\frac{x}{2s-y}+\frac{x}{y}=x(\frac{1}{2s-y}+\frac{1}{y})$$ $$2s=x(\frac{y}{2sy-y^2}+\frac{2s-y}{2sy-y^2})=x(\frac{2s}{2sy-y^2})$$ $$1=\frac{x}{2sy-y^2}$$ $$2sy-y^2=x$$ $$2sy=x+y^2$$ $$s=\frac{x+y^2}{2y}$$ From $z=s^2+3t$ we have: $$z=(\frac{x+y^2}{2y})^{2}+3t$$ $y=s+t$ so $t=y-\frac{x+y^2}{2y}$ and finally: $$z=(\frac{x+y^2}{2y})^{2}+3(y-\frac{x+y^2}{2y})$$ Pretty sure this is correct...

share|improve this answer
2  
Welcome aboard. –  Emre Apr 27 '11 at 5:52

Try to express $s$ and $t$ as functions of $x$ and $y$ from the first two equations. Then plug these expressions into the third equation.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.